Neurotrophic Effects of Iridoid Glycosides From Lamium Album L. as Natural GLP1-R Modulators in Repeated Restraint Stress - ROMAN, Ioana; MOLDOVEANU, Claudia-Andreea; DRĂGAN, Ștefan; BAUMLI, Julia; CIMPOIU, Claudia; TOMA, Vlad-Alexandru (Studia Universitatis Babeș-Bolyai Chemia, 2024)
The pleiotropic effects of Lamium species are extensively utilized for treating urinary bladder injuries and infections and addressing blood hypertension or liver toxicities. Despite widespread Lamium consumption in animals and humans, its impact on brain biochemical parameters remains unexplored. In our study, we demonstrated the regenerative effect of L. album L. in a rat model of restraint stress, commonly employed to investigate neuropsychological stress. Following extract administration, there was a reduction in stress hormones (corticosterone, adrenaline), inflammation (TNFα), and oxidative stress. These neuroregenerative effects may be attributed to Lamium’s phytochemical composition, particularly its iridoids and luteolin content, which appear to mimic the action of glucagon-like peptide 1 (GLP-1). These findings suggest the potential use of L. album as a neuroregenerative adjuvant.